Herpetofauna in two coastal sites in the municipality of Soto la Marina, Tamaulipas, Mexico - Contreras-Lozano, Jorge A.; Lazcano, David; García-Salas, Juan A.; Contreras-Balderas, Armando J. (Instituto de Ecología, A.C., 2013)
We conducted a herpetofaunal study from November 2009 to July 2010 on the ranches El Herradero and San Jose de los Leones, both in the municipality of Soto la Marina, in the centraleastern part of the state of Tamaulipas, northeastern Mexico. Their location corresponds to a peninsula surrounded by the Laguna Madre. The objectives were to conduct a herpetological inventory and to determine the distribution of the species in the plant communities and the status of each species following the criteria of the NOM-059-SEMARNAT-2010. The information will be useful in delineating an area to set aside for conservation easement for the species. We followed the transect method described by Campbell & Christman (1982). We recorded 17 species: one anuran, one crocodile, six turtles, three lizards and six snakes. Of these, eight are new records for the municipality of Soto la Marina, 10 species are at risk, six are of special concern, three are threatened, and one is endangered. The ranches contain 34.69% of the herpetofauna species present in the municipality.